THE EFFECT OF LEADERSHIP STYLE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT ADINDA PERMATA MULIA SOUTH TANGERANG - Sakti Wicaksono (JURNAL ASIK, 2026)
This study aims to analyze the effect of leadership style (X1) and work motivation (X2) on employee performance (Y) at PT Adinda Permata Mulia. The research adopts a quantitative approach with an associative causal design. The population consists of 40 employees, and a saturated sampling technique is applied, resulting in 40 respondents. Data were collected through questionnaires and analyzed using multiple linear regression, t-test, F-test, and coefficient of determination. The results show that leadership style has a positive and significant effect on employee performance, as indicated by a t-value of 8.345 with a significance level of 0.000 (< 0.05). Work motivation also has a positive and significant effect on employee performance, with a t-value of 9.505 and a significance level of 0.000 (< 0.05). Simultaneously, leadership style and work motivation significantly influence employee performance, as evidenced by an F-value of 61.428, which exceeds the F-table value of 3.25, with a significance level of 0.000 (< 0.05). The coefficient of determination (R²) of 0.769 indicates that 76.9% of employee performance is explained jointly by leadership style and work motivation, while the remaining 23.1% is influenced by other variables not examined in this study. The findings conclude that both leadership style and work motivation play a crucial role in enhancing employee performance. Therefore, organizations are encouraged to strengthen leadership practices and implement effective motivational strategies to achieve sustainable performance improvement